Dietary Diversity Score during Pregnancy is Associated with Neonatal Low Apgar Score: A Hospital-Based Cross-Sectional Study - Quansah, Dan Yedu; Boateng, Daniel; Kwantwi, Louis Boafo; Owusu-Sekyere, Anthony; Amegah, A. Kofi (International Journal of Child Health and Nutrition, 2019)
Background: Apgar score is an established index of neonatal well-being and development. Nutrition during pregnancy is an accepted risk factor for neonatal low Apgar score. Objective: To investigate the association between dietary diversity score and low Apgar score. Methods: This was a hospital based cross-sectional study. The study participants were 420 mothers who delivered and were attending the postnatal clinic at the Cape Coast Metropolitan Hospital. Mothers’ dietary information during pregnancy was assessed with a food frequency questionnaire. In reference to the FAOs women’s Dietary Diversity Score (DDS), the subjects were categorized into low, medium or high DDS. The primary outcome was Apgar score. Apgar scores < 5 were classified as low. Results: The mean age (± standard deviation, SD) of subjects was 26.7 ± 5.7 years with a range of 17 to 45 years. The prevalence of low Apgar score among the study population was 16.9%. Majority of the study participants had a low DDS in relation to low Apgar score whereas 7.5% had high DDS. After adjusting for potential confounding factors, the odds of low Apgar score in the low DDS group was three times higher than those who had high DDS (Adjusted odds ratio, AOR= 3.10, 95% confidence interval, CI=1.23-4.48). Conclusion: Dietary diversity score during pregnancy was associated with a low Apgar score in the study area. The results of this study reinforce the significance of adequate nutrition during pregnancy in the study area.